Integrating Cycling with MRT Jakarta for First-Mile and Last-Mile Accessibility: A Stated Preference Approach - Lidya Hotma Silaen; Sutanto Soehodho; Nahry Nahry (Transpublika Publisher, 2026)
Urban mobility in Greater Jakarta is characterized by high commuter volumes between suburban and urban core areas, with daily MRT Jakarta ridership averaging 124,397 passengers in 2025, yet first-mile and last-mile station accessibility remains a persistent challenge. This study evaluates the potential for improving MRT Jakarta accessibility through bicycle integration as first-mile and last-mile modes, and estimates acceptable pricing for public bike-sharing and private bicycle parking. A Stated Preference (SP) approach was employed with 385 respondents within a 3 km radius of Lebak Bulus MRT Station, where the existing access mode was disaggregated into seven categories and compared against private bicycle and bike-sharing alternatives, generating twenty-one utility equations estimated through logistic regression. Each alternative's systematic utility was specified as a function of cost, distance, and travel time, with resulting coefficients translated into a generalized cost function and a mode choice probability and sensitivity analysis. Results indicate strong mode-shift potential across all seven existing-mode groups, with the probability of retaining the existing access mode falling to roughly 2-4% while the combined shift probability to cycling exceeds 95% under improved conditions. Cost exerts a consistently negative and statistically significant effect on cycling choice, confirming that higher fares reduce adoption likelihood, while distance and travel time generally lower utility as expected. Private bicycles show higher selection probability than bike-sharing, though the latter remains a viable complementary alternative. Overall, cycling integration with MRT Jakarta holds strong potential to enhance accessibility, driven by affordable pricing and supportive infrastructure.